Perempuan Dan Perannya Dalam Ekonomi - Marzuki, Sitti Nikmah (An - Nisa`, 2012)
Abstract: Woman in doing itâs role give great contributing to the economy of the family. Women as workers improve the economics of the family. Their role is as a housewife in the family child care. This does not prevent them to work outside. Women have an equally important role in the economy. Itâs starting from farming, a fisherman, working in factories and various world of work. His in involvement was not another to help the family economy resulting in the family welfare.In these roles women contribute their economic improvement, particularly women farmers and fishermen are the backbone of the family. They work from preparing seeds to marketing the corp. Similarly for women who choose the profession of fisherman conduct their activities from fishing to market it. This is done to improve the economy.